Conrad put Asia on the world map - Abd Razak, Dzulkifli (2007)
THANKS to the Polish Embassy and the initiative of its ever energetic ambassador, Malaysians were recently treated to one of the many rich facets of Polish arts and culture. Some Malaysians may be more familiar with Poland's invincible tanks, following our country's decision to acquire the vehicles recently. They may not be aware of Poland' softer side. So, when a superb flutist was flown in to perform at the Universiti Sains Malaysia's Dewan Budaya (Cultural Hall) last week, another window opened. The event showcased the extraordinary performance of Jadwiga Kotnowska, a solo performer of exceptional talent.